العفو عن العقوبة في التشريع الجزائري والكويتي (Revue El-Wahat pour les Recherches et les Etudes, 2021)
Pardon of punishment is not a new criminal system, no State law almost devoid of text to this procedure, as defined by both Algeria and Kuwait, like other countries of the world since antiquity, it is defined as an authority vested in Algeria by the Constitution to the head of State and in Kuwait to the Prince used in national holidays occasions under which exempt the sentenced person from the penalty, either by dropping it in whole or in part or by replacing it with a lighter penalty. Despite widespread amnesty for punishment, also known in some countries under the name "Pardon" or "Presidential Pardon" in all States but not supported by all scholars, so split on the identification of legal nature and retaining it or cancel it or replace it with another criminal system to several directions. Keywords: The presidential pardon- Forgiveness-Presidential Decree-Amnesty.